Jual Beli Bensin Dengan Menggunakan Jerigen - Nasution, Zakiah Khairani (Jurnal El-Thawalib, 2021)
The sale and purchase of gasoline at the Sibuhuan SPBU, Padang Lawas Regency is where the sale and purchase of gasoline using jerry cans at gas stations is carried out by consumers, consumers must pay the contents (additional money) according to the size of the jerry cans they fill. has been issued by the SPBU in order to be able to refill gasoline using jerry cans, namely by bringing a letter of recommendation (suratizin) from the Government. The research method that I use is to use field research (Field Research) which is descriptive qualitative. This research will describe how the practice of buying and selling gasoline using jerry cans at the Sibuhuan gas station, Padang Lawas Regency in terms of the compilation of Islamic economic law. The data collection techniques used were interviews, observation, and documentation. After the researcher obtains the data, the data is processed / analyzed to be re-checked for validity and deductively which is then reported descriptively. The results obtained from this study are not in accordance with the second point of the Islamic Economic Law Compilation, namely the legislation because it contradicts Presidential Regulation No. 191/2014 Article 18 paragraph (2), namely "business entities and / or the community are prohibited from hoarding and / or storing. certain types of fuel that are contrary to the provisions of laws and regulations.